Kelengkapan Rekam Medik Kasus Kekerasan Fisik akibat Tindak Pidana di RSUP Prof. Dr. R. D. Kandou Periode September 2017- Agustus 2018 - Lumentut, Cherryl A.; Kristanto, Erwin G.; Siwu, James F. (JURNAL BIOMEDIK : JBM, 2019)
Abstract: Complete medical record is clearly important to health service of a hospital. In cases of violence, medical records play a significant role in law enforcement. Prof. Dr. R. D. Kandou Hospital is categorized as type A service hospital that has been fully accredited in 2015. Therefore, its medical personnels should be responsible for the completeness of each patient’s medical record, especially of violence cases. This study was aimed to determine the completeness of physical violence cases’ medical records due to criminal acts at Prof. Dr. R. D. Kandou Hospital in the period of September 2017-August 2018. This was a descriptive retrospective study. The results obtained as many as 40 cases of physical violence due to criminal acts. The medical record completeness of physical violence cases due to criminal acts were as follows: in Emergency Care 40%, inpatients 12%, surgery 58.82%, anesthesia/ sedation 45.45%, blood transfusion 66.67%, and informed consent 96.87%. Conclusion: In physical violence cases due to criminal acts, the medical record completeness with informed consent had higher percentage than the other medical record documents.Keywords: completeness of medical record, physical violence casesAbstrak: Kelengkapan rekam medik merupakan hal penting dalam pelayanan kesehatan dari suatu rumah sakit. Dalam kasus kekerasan, rekam medik berperan dalam penegakan hukum. RSUP Prof. Dr. R. D. Kandou sebagai rumah sakit pelayanan tipe A yang telah terakreditasi paripurna pada tahun 2015, sudah seharusnya kelengkapan rekam medis bagi setiap pasien menjadi tanggung jawab tenaga medis terutama rekam medik kasus kekerasan yang ada di RSUP. Prof. Dr. R. D. Kandou. Penelitian ini bertujuan untuk mengetahui kelengkapan rekam medik kasus kekerasan fisik akibat tindakan pidana di RSUP Prof. Dr. R. D. Kandou periode September 2017 - Agustus 2018. Jenis penelitian ialah deskriptif retrospektif. Hasil penelitian mendapatkan sebanyak 40 kasus kekerasan fisik akibat tindak pidana. Secara keseluruhan kelengkapan rekam medik pada kasus kekerasan fisik akibat tindak pidana di Instalasi Rawat Darurat sebesar 40%, rawat inap 12%, tindakan operatif 58,82%, tindakan anestesi/sedasi 45,45%, transfusi darah 66,67%, dan informed consent 96,87%. Simpulan: Pada kasus kekerasan fisik akibat tindakan pidana, kelengkapan rekam medik dengan informed consent memiliki persentase yang lebih tinggi daripada berkas rekam medik lainnya.Kata kunci: kelengkapan rekam medik, kasus kekerasan fisik